Efeito da própolis sobre o crescimento de bacilos gram-negativos móveis coletados em hortifrutigranjeiro - Fabiano, Melina Zuzi (Universidade Federal de São Carlos, 2011)
Currently there is great concern about the quality and food contamination. All food marketed "in nature" may have some kind of contamination by microorganisms can be or not pathogenic for those who consume them. The contamination can occur throughout the production chain until it reaches the final consumer. In addition to the health problem, contamination can contribute to reducing the shelf life of products "in nature." A product that can act in this chain, improving the hygiene of foods such is propolis, that since ancient times has been used to battle infections. Known as a natural antibiotic is widely used in veterinary and human medicine as well as industries such as food, pharmaceutical, cosmetics and others. Propolis is derived from a mixture of plant resins, collected by bees, and its therapeutic action is associated with a high content of flavonoids. In Brazil, the green propolis is considered the that hve best antibacterial efficiency. Thus, this study sought to characterize and identify the action of green propolis, produced in the southern state of Minas Gerais, on gram-negative bacilli collected from horticultural and from results obtained propose a possible form of incorporate extracts of propolis in horticultural production chain for the purpose of cleaning the places where food is transported, stored, and the hygiene of such foods. We evaluated the action of propolis on the bacilli collected by obtaining growth curves in the presence of propolis and the disk diffusion method, with the aim of finding the minimum concentration of propolis extract able to inhibit or delay the growth of these bacilli and that do not change the taste, smell and color of food where the propolis was applied.
Keywords: Microbiologia; Bactérias gram-negativas; Própolis; Bactérias - controle microbiano; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::MICROBIOLOGIA DE ALIMENTOS